Interplay of Knowledge, Ritual, and Science in Islamic Tradition - Dr. Muhammad Abdul Khabeer Sheikh (Corresponding Author); Dr. Muhammad Samiullah (International Research Journal of Arabic and Islamic Studies, 2024)
Islam has long emphasized the pursuit of knowledge as a divine obligation, intertwining spiritual insight with intellectual endeavors. This study explores the Qur'anic foundation for scientific intellectualism, tracing the development of knowledge within Islamic civilization. Beginning with the first revelation, which underscored the significance of reading and learning, the paper examines the subsequent intellectual revolution shaped by the integration of theological, social, and natural sciences. By contextualizing Islamic scientific traditions within the broader framework of Tawhid (the Oneness of God), this research highlights the sacredness of nature as a Divine Sign and humanity's role as its custodian. Furthermore, it underscores the inseparability of science and faith in Islamic thought. By investigating key Qur'anic concepts of knowledge ('ilm), the study offers insights into the unique epistemological framework that has historically driven scientific advancements in Islamic civilization.